Pengaruh Harga dan Kualitas Pelayanan Terhadap Minat Beli Ulang pada Toko Bangunan Jaya Abadi Selebung Kecamatan Keruak Kabupaten Lombok Timur: The Influence of Price and Service Quality on Repurchase Interest in Jaya Abadi Selbung Building Store, Keruak Sub-District, Lombok Timur District - Lalu M. Furkan (LPPM Institut Studi Islam Sunan Doe, 2022)
The Effect Of Price and Quality Service For Buying Interest Repeat at The Toko Bangunan Jaya Abadi Selebung Kecamatan Keruak Kabupaten Lombok Timur. The study aims to determine The Effect Of Price and Quality Service For Buying Interest Repeat at The Toko Bangunan Jaya Abadi Selebung Kecamatan Keruak Kabupaten Lombok Timur. The Population in this study were consumer who had made a purchase at the Jaya Abadi Building Store, while the sample of this study was 50 using purposive sampling technique. This type of research is an associative research. Data processing in this study using SPSS 25.0 for windows. Were the validity test, reliability test, classical assumption test is carried out. Multiple linier regression analysis test, test significance (t test) and test the coefficient of determination (R2). Based on the results of the study, it shows that: (1) Price has a positive and significant effect on repurchase intention (2) Service quality has a positive and significant effect on repurchase interest.